Promoting Sustainable Enterprise & Human Resource Development in Rural Kenya: A Cooperative Approach - Prieto, Leon C.; Wairimu, James; Ndinguri, Erastus N.; Kungu, Kenneth K. (Journal of Leadership, Accountability and Ethics, 2020)
There is an urgent need to promote sustainable enterprise and human resource development in order to create thriving rural communities and solve some of the problems facing Kenya such as poverty and under-employment. Rural areas face such challenges as resource constraints, lack of needed infrastructure, inability to attract large employers, availability of local talent, among others, that limit the range of economic development strategies available to rural areas. This paper makes suggestions on how to promote cooperative-modelled entrepreneurial structures, building on the existing tradition of relying on self-help groups and cooperatives for job creation and economic empowerment in rural communities.